A Escola Betine em MS: (Des) Caminhos da educação nos presídios - ELIANA DORACI DA SILVA (2021)
This study investigates the bases of implementation of the State School Polo Profª Regina Lúcia Anffe Nunes Betine (Escola Betine) in the existing school extensions in male prisons of closed regime in the city of Campo Grande: Penal Institute of Campo Grande (IPCG), Triage Center "Anísio Lima" (CTAL) - medium security penal units, and the Penal Establishment "Jair Ferreira de Carvalho" (EPJFC), maximum security penal unit, in the period from 2003 to 2019. Based on Michel Foucault's references and by means of bibliographic and documental research, observation and semi-structured interviews, we sought to describe the bases of the history that was consolidated by this school institution, considered the first Brazilian public school regulated to attend the prison population and its proposals in face of the statements of social reinsertion through education, emphasized in interviews and reports made available in the media. The research made possible the mapping of the institutions that attended the prison population in these prisons before and after its creation and the verification of the conditions of the school spaces in prisons, being able to subsidize those responsible in the elaboration of a political-pedagogic project that contemplates the specificities of schooling in prisons. The results indicate that the Betine School is no longer exclusive in the attendance to the penitentiary system of the state of Mato Grosso do Sul and that the professionalizing education is added to the regular education offered in the extensions of the school with focus on the resocialization and valorization of labor. Keywords: Schooling in Prisons; Trajectory; Penitentiary System.